CERMIN DIRI DALAM KARYA SENI LUKIS - Alvino Hasan; Idran Wakidi; Syafril . (Serupa The Journal of Art Education, 2012)
Abstract Search of self identity is something that very important in our lives: about who we are what we life3 for, and the purpose of life it self. The purpose of this final work is (1) as container to implement the skill and painting skills are displayed in the form of the final work (2) provide insight in addressing the conditions of feelings and problems that is experienced. This final work is the form of paintings that show realism and surrealis style. Realization of this work is the result of contemplation observation then visualized into line, clour and shape of the object that desired, so creating a work as an expression and out povring of the heart to wards the problem that occurred.   Keywords : Mirror, self, work, painting